The Impact of Health Behaviors on Iron Supplementation Adherence and Anemia Prevalence among Pregnant Women: Evidence from a Primary Care Setting in Aceh Tengah, Indonesia - Nova Ratna Dewi; MS, Sri Wahyuni; Hidayana (HM Publisher, 2024)
Anemia during pregnancy remains a significant global health concern, particularly in developing countries like Indonesia. However, adherence to iron supplementation programs is often suboptimal, leading to persistent anemia and adverse maternal and neonatal outcomes. This study aimed to investigate the relationship between health behaviors (knowledge, attitudes, and practices) and adherence to iron supplementation among pregnant women in a primary care setting in Aceh Tengah, Indonesia. Additionally, we explored the impact of these factors on anemia prevalence. A cross-sectional study was conducted at the Pegasing Community Health Center in Aceh Tengah, Indonesia. Pregnant women diagnosed with anemia were recruited, and data were collected using questionnaires assessing their knowledge, attitudes, and practices regarding iron supplementation. Hemoglobin levels were measured to determine anemia status. Statistical analyses were performed to examine the relationships between health behaviors, adherence, and anemia prevalence. A total of 59 pregnant women with anemia participated in the study. Adherence to iron supplementation was suboptimal, with 59.3% reporting poor adherence. Knowledge about iron supplementation was generally good (76.3%), but attitudes and practices were less favorable (30.5% and 27.1%, respectively). Statistical analyses revealed a significant association between attitudes and practices related to iron supplementation and adherence. Furthermore, poor adherence was linked to a higher prevalence of anemia. In conclusion, healthy behaviors, particularly attitudes and practices, play a crucial role in iron supplementation adherence among pregnant women in Aceh Tengah, Indonesia. Interventions targeting these behaviors are essential to improve adherence and reduce the burden of anemia in this population.